Biocompatible Gold Nanorod Conjugates for Preclinical Biomedical Research - Liopo, Anton (2012)
Gold nanorods with a peak absorption wavelength of 760 nm were prepared using a seed-mediated method. A novel protocol has been developed to replace hexadecyltrimethylammonium bromide on the surface of the nanorods with 16-mercaptohexadecanoic acid and metoxy-poly(ethylene glycol)-thiol, and the monoclonal antibody HER2. The physical chemistry properties of the conjugates were monitored through optical and zeta-potential measurements to confirm surface chemistry changes. The efficiency of the modifications was quantified through measurement of the average number of antibodies per gold nanorod. The conjugates were investigated for different cells lines: BT-474, MCF7, MCF10, MDCK, and fibroblast. The results show successful cell accumulation of the gold nanorod HER2 conjugates in cells with HER2 overexpression. Incubation of the complexes in heparinized mouse blood demonstrated the low aggregation of the metallic particles through stability of the spectral properties, as verified by UV/VIS spectrometry. Cytotoxicity analysis with LDH release and MTT assay confirms strong targeting and retention of functional activity of the antibody after their conjugation with gold nanorods. Silver staining confirms efficient specific binding to BT-474 cells even in cases where the nanorod complexes were incubated in heparinized mouse blood. This is confirmed through in vivo studies where, following intravenous injection of gold nanorod complexes, silver staining reveals noticeably higher rates of specific binding in mouse tumors than in healthy liver. The conjugates are reproducible, have strong molecular targeting capabilities, have long term stability in vivo and can be used in pre-clinical applications. The conjugates can also be used for molecular and optoacoustic imaging, quantitative sensing of biological substrates, and photothermal therapy.